JHEA, Volume 14, n°2, 2016 - Full Issue - system, journal (Journal of Higher Education in Africa, 2021)
Contents Research-based Honours Degrees: The Perspective of Bachelor of Commerce Students at the University of South Africa Edmund Ferreira & Sumei van Antwerpen...................................1 La réforme LMD au Sénégal : le point de vue des étudiants Babacar Diop................................................... 21 Introducing Open Source Reference Management Software to a Rural South African Campus: Evaluating the Effectiveness of Workshops at the University of the Free State’s Qwaqwa Campus Aliza le Roux & Diana Breshears...................................... 49 La gouvernance des universités au Sénégal : une grande réforme, mais pas une rupture Diène Colly Ousseynou Diouf.............................. 61 The Exploration of Service Quality Leadership for Private Higher Education Institutions in South Africa Riaan Dirkse van Schalkwyk & Rigard J Steenkamp...................... 85 Brief Assessment of Higher Education Governance in Ethiopia:Reflection on the Leap of the Decade Anteneh Melu................................................... 107